The Origin and the Overcoming of Evil and Suffering in the World Religions
VII, 159 p.
Keywords: All religions face the challenge of explaining, in view of God's goodness, the existence of evil and suffering in the world. They must develop theories of the origin and the overcoming of evil and suffering. The explanations in Buddhism, Christianity, Hinduism, Islam, and Judaism of evil and suffering and their origin, as well as these world religions' theories of how to overcome evil and suffering, differ from one another, but are also similar in many respects. The human person is always considered to be the origin of evil, and also to be the focus of aspirations to be able to overcome it. The conviction that evil and suffering are not original and can be overcome is characteristic of and common to the religions. The explanations of the origin of evil are closely related to the explanations of the continuation and propagation of evil in human persons, in nature, and in our technology and culture that have been developed in the religions - in Christianity, for example, as the doctrine of original sin. Finally, the world religions are concerned with how to cope with suffering and offer guidance for overcoming evil and suffering. Leading scholars of five world religions, Buddhism, Islam, Christianity, Judaism, and Hinduism, have created with this volume a first-hand source of information, which enables the reader to gain a better understanding of these religions' central teachings about the origin and the overcoming of evil and suffering.